Electroacupuncture alleviates functional constipation by upregulating host-derived miR-205-5p to modulate gut microbiota and tryptophan metabolism - Wang, Lu; Xi, Menghan; Cao, Wei; Qin, Haiyan; Qin, Di; Chen, Shuai; Zhou, Siyuan; Hou, Yujun; Chen, Ying; Xiao, Xianjun; Zheng, Qianhua; Li, Dehua; et al. (Frontiers in Microbiology, 2025)
Electroacupuncture (EA) has shown promise as a treatment for Functional constipation (FC), with growing evidence suggesting it may enhance gut motility. MicroRNAs (miRNAs) serve as key regulatory molecules mediating host-microbiota interactions. However, the specific fecal miRNAs regulating microbiota composition and metabolism in EA-treated constipated mice, along with their key targets, remain unidentified. We examined fecal microbiome composition, metabolism, and colonic miRNA expression in loperamide-induced constipated mice and EA-treated mice to identify differentially expressed miRNAs and assess their relationships with microbial abundance, metabolism, and gut motility. An antibiotic cocktail and adeno-associated virus were employed to interfere with the gut microbiota and target miRNA in vivo, thereby validating the proposed mechanism. Our results indicate that miR-205-5p, significantly upregulated in fecal and colonic tissues of EA-treated constipated mice, promotes intestinal motility in a microbiome-dependent manner. Specifically, EA promoted the growth of Lactobacillus reuteri, enriched in the feces of constipation-recovered mice, through host-derived miR-205-5p regulation. Furthermore, Lactobacillus reuteri and its tryptophan metabolites (indole-3-acetamide, indole-3-acetic acid, and indole-3-carboxaldehyde) alleviated loperamide-induced constipation. These findings underscore the pivotal role of host-derived miR-205-5p in modulating microbial composition and tryptophan metabolites to enhance intestinal motility through EA.